1977
DOI: 10.1103/physrevd.15.854
|View full text |Cite
|
Sign up to set email alerts
|

Ideal mixing for baryons

Abstract: We suggest that all configuration mixing within the 3 1-multiplet of SU(6) X O(3) is governed by simple decoupling conditions. We deduce a tentative set of ideal mixing angles and discuss the kind of models that might lead to such mixing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
3

Year Published

1978
1978
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
12
3
Order By: Relevance
“…The angle θ 3 remains ambiguous and close to the values obtained in the LO fits. It should be noticed that the present values of both mixing angles are somewhat different from the values θ 1 = 0.61, θ 3 = 3.04 obtained in other analyses [10,16,20].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The angle θ 3 remains ambiguous and close to the values obtained in the LO fits. It should be noticed that the present values of both mixing angles are somewhat different from the values θ 1 = 0.61, θ 3 = 3.04 obtained in other analyses [10,16,20].…”
Section: Resultscontrasting
confidence: 99%
“…The mixing angles θ 1 = 0.39 ± 0.11 and θ 3 = (2.82, 2.38) ± 0.11 that result at NLO are similar to the ones determined at LO. They are , however, somewhat different from the angles θ 1 = 0.61 and θ 3 = 3.04 obtained in other analyses [10,16,20].…”
Section: Discussioncontrasting
confidence: 91%
“…In this paper, we show how to apply these ideas to hadronic decays of the orbitally excited baryons in the SU (6) 70-plet [9,10]. In the Hartree language, these are states with Nc -1 quarks in the ground state of the Hartree potential, and one quark in an orbitally excited state.…”
Section: Introductionmentioning
confidence: 99%
“…Rosner et al discussed some qualitative effects of SU(6) w-like and anti-SU (6) w-like currents in connection with the signs of amplitudes derived from nN----'> nnN phase-shift analysis. 16 However, the predicted magnitudes are not consistent with the results of phase-shift analysis, for example, 18 J as seen in the p1 and p3 amplitudes of P P11 (1730) and P P13 (1700) partial waves. *J *J The notation used for describing our partial wave amplitude is as follows.…”
mentioning
confidence: 89%
“…It has been concluded that higher-symmetry approaches have some difficulty and the relativistic quark model is found to fail in reproducing relative phases of resonant amplitudes. 4 J' 16 J Before discussing our model, we briefly review higher-symmetry approaches in the present problem. Since Lipkin and Meshkov proposed the SU(6) w symmetry 1 n in 1965, the broken SU (6) w,12l the 3 P 0 modeP 3 J and the Melosh transformation 14 J have been proposed in the framework of the SU(6) w symmetry.…”
mentioning
confidence: 99%